Numerical modelling of reinforced concrete beams with fracture-plastic material - O. Sucharda; J. Brozovsky (Fracture and Structural Integrity)
This paper describes the use of models of fracture-plastic materials for reinforced concrete in numerical modelling of beams made from reinforced concrete. The purpose of the paper is to use of a model of concrete for modelling of a behaviour of reinforced concrete beams which have been tested at the University of Toronto within re-examination of classic concrete beam tests. The original tests were performed by Bresler- Scordelis. A stochastic modelling based on LHS (Latin Hypercube Sampling) has been performed for the reinforced concrete beam. An objective of the modelling is to evaluate the total bearing capacity of the reinforced concrete beams depending on distribution of input data. The beams from the studied set have longitudinal reinforcement only. The beams do not have any shear reinforcement. The software used for the fracture-plastic model of the reinforced concrete is the ATENA.